al-Isykalat al-Nazhariyah Fi Ta’lim al-Nahw wa al-Sharf Li al-Nathiqin Bighair al-Arabiyah Fi Indonisia - Akzam, Ismail; Hamawiya, Adham (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This study aim’s to the Arabic education institutes in Indonesia who think that as-sarhf teaching precedes an-nahw teaching, while others see an-nahw teaching precede pure education, and the two parties forget that the generalization of each of them is not straightforward; the learner from Arabic speakers is not the same as the learner from other speakers, and is specialized in the Arabic language and its literature not like a specialist in other sciences, and it is not correct for these scholars and specialists to be prepared either, but social and professional differences between them are taken into account, so the difference is clear between learning Arabic in its countries and between it in others, as well as between its learning because it is an end and it is because it is a means, which necessitates reviewing some problems the theory of the trade-off between an-nahw and as-sarhf and their teaching for non-Arabic speakers, especially in Indonesia, and we have discussed this issue through a critical approach, and we have come to the conclusion that the solution to obtain competence and integrated language skills is to combine an-nahw and as-sarhf teaching according to certain conditions that go beyond the problems experienced in the development Teaching Arabic in Indonesia, and at the forefront of these problems is reliance on traditional curricula, lack of comprehensive courses and modern teaching methods, as well as insufficient qualification of teachers sufficient and professionally, and relying on courses that do not match the level of Learners and their needs, in addition to the educational content lacking the pedagogical, psychological and cultural linguistic foundations, whether in its choice or its organization.